Promoting and protecting values through leadership agency: : Experiences from disaggregation and autonomisation of municipal waste management - Andersen, Ole Johan; Torsteinsen, Harald (Scandinavian Journal of Public Administration, 2016)
The disaggregation and autonomisation of public service procurement have been at the leading edge for the last two to three decades, not least due to the importance which New Public Management (NPM)-inspired reform programs have acquired. Rather than rejecting such organisational tools, we attempt to revea lthe complexity of the transformation of a municipal service-providing organisation with relatively delimited, clear-cut aims. Not only do we address issues related to how the transformation proceeded, but also more analytically challenging questions of why it was feasible to accomplish such a complex process in a relatively short period. Our focus on how and why issues favours a single case study design, and we have chosen a waste collecting and processing organisation that was devolved step-by-step from the municipal political-hierarchical system of governance. When approaching the how issues we draw on the analytic framework laid down by Ibarra et al. (2010). However, regarding the important why issues we find Selznick’s (1957/1984) notion of institutional leadership to offer useful clarification.